How Leadership Style Influence Achievement Work - Yudiani, Ema (Journal of Management, 2024)
The goal of this study is to examine the impact of situational leadership style on employee job performance. This study employs a quantitative technique and a saturation sampling strategy due to the small population size of less than 97. This study hypothesis was answered using simple linear regression, correlation coefficient, and coefficient of determination. The findings of this study indicate that situational leadership style has a favorable and substantial impact on employee job performance